2015
DOI: 10.1002/pc.23831
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cellulose nanowhiskers on the properties of poly(vinyl alcohol)/graphene nanoplatelets nanocomposites

Abstract: Cellulose nanowhisker (CNW) is a kind of ideal reinforcing filler due to its biodegradability and renewability together with superior mechanical properties. CNW hybridization with graphene nanoplatelet (GN) incorporated into poly(vinyl alcohol) (PVA) films were produced by ultrasonication mixing prior to solution casting. CNW showed positive effects on the PVA/GN composite films, which improved the dispersion of GN and refined GN by replacing partial GN with CNW in PVA/ GN composite films. The addition of CNW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Comparing Fig. a, b, stretching frequency at 3408 cm −1 of neat PVA gets blue shifted to 3290 cm −1 for PVA‐1MCC, indicating the disruption of hydrogen bond existed in PVA film and possibility of formation of new hydrogen bond between OH groups of PVA and MCC due to sonication . For PVA‐3MCC from Fig.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Comparing Fig. a, b, stretching frequency at 3408 cm −1 of neat PVA gets blue shifted to 3290 cm −1 for PVA‐1MCC, indicating the disruption of hydrogen bond existed in PVA film and possibility of formation of new hydrogen bond between OH groups of PVA and MCC due to sonication . For PVA‐3MCC from Fig.…”
Section: Resultsmentioning
confidence: 81%
“…It was found that the XRD pattern Fig. a of 5PVA film contains a narrow peak at 2 θ 19.4°, and broad peaks at 22.5° and 28.5° corresponding to the characteristic semi crystalline nature of pure PVA . From Fig.…”
Section: Resultsmentioning
confidence: 94%
“…First, the CNWs could stably disperse in the water because of the negative charges on their surfaces, as illustrated in Figure (h). At the same time, the strong adsorption between the CNWs and GN through molecular interactions was favorable for the good dispersion of GN, as shown in Figure (i). We observed that a lot of CNWs randomly absorbed onto the surface of GN sheets, as shown in Figure (k).…”
Section: Resultsmentioning
confidence: 91%
“…First, the CNWs extracted from linen fibers on the basis of the acid hydrolysis method, as previously reported, were diluted with DI water and ultrasonicated for 20 min to obtain a homogeneous aqueous dispersion, as shown in Figure (a,b). The CNWs were extracted from bleached linen with acid hydrolysis methods.…”
Section: Methodsmentioning
confidence: 99%